Ações preventivas da violência : uma análise do Centro Integrado de Cidadania de Vitória à luz da teoria de modelos de produção - Cordeiro Júnior, Almir (2005)
With this research it was intended to identify the organizational and service operations management models that exist on the Centro Integrado de Cidadania de Vitória (CIC-Vitória) and compare these with another one theoretically built from propositions of